The Role of Grasses in Soil Erosion Control (A Case Study of Bakhmal District, Jizzakh Region) - Shermanov, Beknazar O. (American Journal of Biology and Natural Sciences, 2025)
In recent years, soil erosion has become one of the major environmental issues in the foothill and semi-desert zones of Uzbekistan, leading to significant declines in agricultural productivity. This study evaluates the effectiveness of biological measures—particularly grasses with deep and dense root systems—in reducing soil erosion under the conditions of the Bakhmal District. Based on a comparative analysis of scientific literature and field data, four species—Vetiveria zizanioides, Agropyron cristatum, Festuca valesiaca, and Bassia prostrata—were identified as the most efficient biological agents for erosion control. Modeling using the approaches of Wu et al. (2010) and Huang et al. (2010) demonstrated that contour planting of grasses at 20–40 m intervals can reduce surface runoff by up to 80% and wind erosion by 50%. The root systems of Vetiveria zizanioides and Agropyron cristatum increased soil shear resistance by 20–35% and improved infiltration rates, while Bassia prostrata reduced deflation in arid and saline areas by 40–60%. The integration of species with different root architectures enhanced soil stability, moisture retention, and humus regeneration. The research confirms that biological methods are economically viable, ecologically sustainable, and long-lasting compared to engineering solutions. Implementing mixed grass barriers is recommended as a key element in regional soil conservation and anti-desertification programs.